GENDER PECULIARITIES OF THE OSTEOPENIC SYNDROME IN THE DEPENDENCE ON THE RHEUMATOID INFLAMMATION ACTIVITY - Tatyana Alekseyevna Raskina; M V Letaeva (Современная ревматология, 2010)
Objective. The gender differences estimation of mineral bone density (MBD) dependence on the rheumatoid inflammation activity degree. Subjects and methods. 132 patients with the significant RA diagnose are included into the research among them there are 80 males (the main group), 28 females with retained menstrual cycle, 24 females in post-menopause. The control group (for the main) is 84 males without RA compared by the age. MBD was measured by the method of double-energetic absorptiometry with the help stationary radiological double-energetic bone densitometer Exceell XR-46 (Norland, USA). Results. The patients with RA had the significant decreasing of T-criteria and MBD in comparison with indexes of the control group. The average meaning of densitometric indexes at the males with the 3rd activity degree were significantly lower than at the males with the 2nd activity degree. The most risk of osteoporosis (OP) development has been noted at the males and females in post-menopause at the 3rd activity degree. RA at the males is reasonable to consider as a prognostic marker of unfavorable influence on MBD and high activity as a risk factor of OP development associated with the disease itself.